Faktor Risiko Diabetes Melitus Tipe II pada Wanita Kelompok Umur ≥15 Tahun di Indonesia Analisis Data Survei Kesehatan Indonesia 2023 - Syahlia Magdalena Br. Torus; Rd. Halim; Marta Butar Butar; Muhammad Syukri (Universitas Muhammadiyah Manado, 2026)
Type 2 Diabetes Mellitus (T2DM) is a public health problem with a continuously increasing prevalence, and it is higher in women than in men. This study aimed to analyze the risk factors for T2DM in women aged ≥15 years in Indonesia based on data from the 2023 Indonesian Health Survey. This study was a secondary data analysis with a cross-sectional design involving 346,760 women who met the inclusion criteria. Univariate and bivariate analyses were performed using the Chi-Square test with calculation of the Prevalence Odds Ratio (POR) at a 95% confidence level. The results showed the prevalence of T2DM was 1.3%. Factors significantly associated included age ≥40 years (POR=22.4), low education level (POR=1.34), unemployed status (POR=1.18), urban residence (POR=1.91), mild physical activity (POR=1.15), obesity (POR=1.27), and overweight (POR=1.27). Protective factors included vigorous physical activity (POR=0.77) and underweight BMI (POR=0.65), while marital status was not significantly associated (p=0.135). T2DM in women is a multifactorial disease influenced by the interaction of biological, social, behavioral, and environmental factors, thus requiring risk-based promotive and preventive interventions.